Cultural Engagement in Teaching and Learning Foreign Language - Rustan Santaria (Fakultas Tarbiyah dan Ilmu Keguruan, 2020)
The purpose of this study is to describe the foreign language learning in Indonesia, starting at the junior high school level from grade one to tertiary level. But it does not show development and progress and meaningful effectiveness. This research applies the method of autoethnography. Data collected through the retrospection of the author's personal experience and the narrative expressions of the experiences of others were analyzed using descriptive - qualitative methods and techniques. The results of the analysis of this study indicate that although education and learning of foreign languages have a long duration in Indonesia, they do not show satisfactory results. The reason is that foreign language learning is assumed to be mere knowledge. Not a practical skill that requires cultural experience taught in the target languages. Therefore, it is recommended that education policymakers and teachers in Indonesia should make various efforts to consider the component of practical skills in the use of foreign languages in the form of cultural engagement.